Myeloid‐derived suppressor cells in malignant melanoma. (28th September 2014) - Umansky, Viktor; Sevko, Alexandra; Gebhardt, Christoffer; Utikal, Jochen
Summary Melanoma is known for its rapid progression, metastasis to distant organs and therapeutic resistance. Despite high melanoma immunogenicity, the results of immunotherapeutic clinical studies are mostly unsatisfactory. One explanation is the development of strong immunosuppression mediated by highly immunosuppressive regulatory leukocytes, in particular, myeloid‐derived suppressor cells (MDSCs). These cells were found to be enriched and activated in the melanoma microenvironment, inducing a profound impairment of anti‐tumor immune responses and leading to the tumor progression. Therefore, understanding the mechanisms of MDSC generation, migration to the tumor site and activation as well as their targeting is important for the development of novel strategies for effective melanoma immunotherapy. We suggest that such therapeutic approaches should involve the inhibition of MDSC‐mediated immunosuppressive melanoma microenvironment combined with other immunologic treatments.